Transition From Crawling to Walking Changes Gaze Communication Space in Everyday Infant-Parent Interaction - Yamamoto, Hiroki; Sato, Atsushi; Itakura, Shoji (Frontiers in Psychology, 2020)
Acquisition of walking changes not only infants' locomotion itself but also infants' exploratory behavior and social interaction, such as gaze communication. To understand the ecological context in which gaze communication occurs and how it changes with walking development from the point of view of the spatial arrangement of infants, parents, and objects, we analyzed longitudinal data of daily eye contact scenes recorded from head-mounted eye trackers worn by parents as infants grew from 10 to 15.5 months, focusing on infant-parent distance and the number of objects between the dyad. A Bayesian state-space model revealed that the interpersonal distance at which infants initiated eye contact with their parents increased with the time ratio of walking to crawling. This result could not be explained by the developmental change in the amount of time that the infants were far from the parents, which is not limited to the gaze communication context. Moreover, the interpersonal distance at which the parents initiated eye contact with the infants did not increase with the time ratio of walking to crawling. The number of objects on the floor between infants and parents at the time of eye contact increased with interpersonal distance. Taken together, these results indicate that the transition from crawling to walking changes the ecological context in which infants initiate gaze communication to a visual environment characterized by a larger interpersonal distance and, therefore, more objects cluttered between the dyad. The present study has wider implications for the developmental change of shared attention in conjunction with walking development.